2015
DOI: 10.1371/journal.pone.0127726
|View full text |Cite
|
Sign up to set email alerts
|

Clinic Network Collaboration and Patient Tracing to Maximize Retention in HIV Care

Abstract: BackgroundUnderstanding retention and loss to follow up in HIV care, in particular the number of people with unknown outcomes, is critical to maximise the benefits of antiretroviral therapy. Individual-level data are not available for these outcomes in Australia, which has an HIV epidemic predominantly focused amongst men who have sex with men.Methods and FindingsA network of the 6 main HIV clinical care sites was established in the state of Victoria, Australia. Individuals who had accessed care at these sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 14 publications
(15 reference statements)
0
29
0
Order By: Relevance
“…Tobias et al [10] noted that subjects with poorer mental health scores were less likely to be retained in care. McMahon et al [18] further noted that active psychiatric illness at the last clinical visit was associated with not returning for care. Conversely, Blank et al [19] noted in their study that those who reported at least 14 “mentally unhealthy” days per month were more likely to remain retained in care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobias et al [10] noted that subjects with poorer mental health scores were less likely to be retained in care. McMahon et al [18] further noted that active psychiatric illness at the last clinical visit was associated with not returning for care. Conversely, Blank et al [19] noted in their study that those who reported at least 14 “mentally unhealthy” days per month were more likely to remain retained in care.…”
Section: Resultsmentioning
confidence: 99%
“…Health beliefs appear to play an important role, and include feeling hopeless about treatment for HIV [19], or feeling well and being too busy [18]. In addition, perceiving ‘wellness’ as a barrier to seeking treatment, not trusting the medical system or not ‘bothering’ because there is no cure were identified by Tobias et al [10] as relevant beliefs which impacted retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve outcomes for women diagnosed with HIV in Victoria, all are actively followed up by public health officers at the Victorian DHHS to ensure they are linked into care; however, data from this program were not available. A Victorian study aiming to understand retention and loss to follow‐up in HIV care estimated that between 91% and 99% of Victorians diagnosed with HIV were retained in care 29 . These results were not available by gender, however, and included HIV clinical care sites that were all based in metropolitan areas of Victoria, while 16% of WLHIV live in regional Victoria.…”
Section: Discussionmentioning
confidence: 99%
“…A Victorian study aiming to understand retention and loss to follow-up in HIV care estimated that between 91% and 99% of Victorians diagnosed with HIV were retained in care. 29 These results were not available by gender, however, and included HIV clinical care sites that were all based in metropolitan areas of Victoria, while 16% of WLHIV live in regional Victoria. Data from Victorian laboratory sentinel surveillance estimated that 87% of WLHIV receiving an HIV viral load test had an undetectable viral load in 2014.…”
Section: Discussionmentioning
confidence: 99%